2022
DOI: 10.1002/ajhb.23787
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk factors distribution and clustering across different geographic levels in Nepal

Abstract: Background: In an effort to reduce the burgeoning problem of cardiovascular diseases (CVD), it is imperative to understand the variation of risk factors across different geographic regions. This study aims to shed light on examining the leading risk factors of CVD and it's clustering across Nepal.Methods: Data from a nationally representative survey were analyzed to estimate the distribution of four major risk factors (high blood pressure, overweight, obesity, and smoking) of cardiovascular diseases. Similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Our results show different levels of urbanization are associated with differential chronic disease risk, as found elsewhere (Ghimire et al, 2022; Kidokoro et al, 2022). However, it is important to state that while we observed that rural and more isolated living was associated with overall better chronic disease risk profiles, quilombos —including those in more rural environments—historically and presently are facing hardships that continue to impact their health.…”
Section: Discussionsupporting
confidence: 90%
“…Our results show different levels of urbanization are associated with differential chronic disease risk, as found elsewhere (Ghimire et al, 2022; Kidokoro et al, 2022). However, it is important to state that while we observed that rural and more isolated living was associated with overall better chronic disease risk profiles, quilombos —including those in more rural environments—historically and presently are facing hardships that continue to impact their health.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the restrictions on hunting, fishing, and the reduction of their lands by predatory entrepreneurship have been forcing changes in the lifestyle of the quilombolas, who were traditionally involved in subsistence agriculture (Shiraishi Neto 2007;Nunes et al 2016;Silva et al 2016). It is worth noting that a higher level of urbanization, linked to a shift to a capitalist economy, is related to more sedentary lifestyles, higher stress, and a decrease in dietary quality, associated with increased chronic disease risk (Wells 2012; Ghimire et al 2022;Kidokoro et al 2022). Brazilian quilombos are not exempt from this pattern, with more urbanized quilombos showing higher chronic disease-related risk factors than their urban counterparts (Paiva et al 2022).…”
Section: The Genetics Of Health-related Traits In Quilombos and The I...mentioning
confidence: 99%